Individual Report: Predictive Analytics - Avasthi, Aditya (2013)
Today’s economy can be defined as knowledge based economy. Survival in such type of an economy depends on the ability to convert information into knowledge. It is estimated that in the next three year more data or information will be generated than last one thousand years. Large amount of data or information is available online. The available information must be converted to knowledge to improve decision making and stimulate innovation.